Virtual Geosites as Innovative Tools for Geoheritage Popularization: A Case Study from Eastern Iceland - Federico Pasquaré Mariotto; Fabio Luca Bonali (Geosciences, 2021)
In this paper, we have adopted a modern, cutting-edge methodology to make geoheritage sites (geosites) available and explorable worldwide, through both immersive and non-immersive virtual reality, particularly suitable also in COVID-19 times. In doing this, we have focused our attention on five different outcroppings, shallow magma bodies in Iceland: such geological objects, although being often underestimated, are, on the contrary, very suitable for geoheritage popularization purposes. These outstanding outcrops have been transformed in virtual outcrops (VOs) through UAV-based photogrammetry 3D modelling, and have been uploaded on a brand-new, dedicated online resource (GeoVires Virtual Reality Lab for Earth Sciences) which is accessible worldwide for Earth Science teaching and communication. As already stressed above, the choice of these Icelandic shallow magma bodies has been suggested by the fact that such geological objects, although extraordinarily challenging both in terms of geotourism and teaching, are seldom the object of attention from the international scientific community. The five VOs are defined here as virtual geosites (VGs) because they are, indeed, geosites that are fully accessible with a smartphone, a tablet, or a PC; moreover, each is provided with a detailed description and notes available during 3D exploration. Our work could represent a model for future, similar efforts aimed at popularizing Earth Sciences and making geoheritage available to a broad public through VGs.